2008
DOI: 10.1002/jbm.b.31176
|View full text |Cite
|
Sign up to set email alerts
|

Multinozzle low‐temperature deposition system for construction of gradient tissue engineering scaffolds

Abstract: Tissue engineering is a technology that enables us to construct complicated hominine organs composed of many different types of cells. One of the key points to achieve this goal is to control the material composition and porous structure of the scaffold accurately. A disposable syringe based volume-driven injecting (VDI) nozzle was proposed and designed to extrude both natural derived and synthetic polymers. A multinozzle low-temperature deposition and manufacturing (M-LDM) system is proposed to fabricate scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The main components of this system is a digital micro-mirror projection (DLP) array (Texas Instruments) which can be loaded with any user-defined bitmap files to make virtual digital masks, which selectively switch mirrors into either the ON state or the OFF state (Fig. [50][51][52][53] The ON state reflects the UV light into the focusing lens, which projects the image into the liquid prepolymer solution, while the OFF state diverts the UV light away from the prepolymer solution.…”
Section: Biocompatibility Of Pegda-panimentioning
confidence: 99%
“…The main components of this system is a digital micro-mirror projection (DLP) array (Texas Instruments) which can be loaded with any user-defined bitmap files to make virtual digital masks, which selectively switch mirrors into either the ON state or the OFF state (Fig. [50][51][52][53] The ON state reflects the UV light into the focusing lens, which projects the image into the liquid prepolymer solution, while the OFF state diverts the UV light away from the prepolymer solution.…”
Section: Biocompatibility Of Pegda-panimentioning
confidence: 99%
“…Recent stratified interfacial designs have focused on porosity or pore size, 21,37,38,66 matrix proteins, 37,43,61,62,67 mineral, 37,38,61,62,67 and bioactive factor 62 incorporation to resolve transitioning orthopedic tissue structures. There also exist stratifications of cell types 2,14,33 or other features 7,20,24,27,63,71 for vasculature network interface formation.…”
Section: Stratified Interfacesmentioning
confidence: 99%
“…Similarly, Liu et al 37 used multinozzle low-temperature deposition manufacturing (M-LDM) with collagen type I, chitosan, gelatin, TCP, and poly(D,L-lactic- co -glycolic acid) (PLGA) to create extremely complex interfacing surfaces for use with virtually any tissue engineering application (Table 1). Scanning electron microscopy (SEM) revealed that integration between natural and synthetic polymers was feasible, and the authors highlighted the ability to possibly interface materials with differing hydrophilicities, which could influence fluid dynamics, nutrient exchange, and biodegradation within any given construct.…”
Section: Stratified Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Soaking in SBF showed the composites to have higher bone bioactivity than the non-filled polymer. Liu and colleagues [38,39] used PLLA, PLDLA and PGA all reinforced with 30 or 50wt% TCP and then used a combination of low temperature deposition to produce macropores or channels through the materials and freeze drying to produce micropores. In a series of purely mechanical tests they optimised the production route.…”
Section: Porous Manufacturementioning
confidence: 99%